Kajian Struktur Modal Sub Sektor Kosmetik dan Keperluan Rumah Tangga Periode 2015-2020 - Pratiwi, Anggi Saktiya; Giovanni, Axel (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2022)
Organizations can improve quality by managing their capital structure. The capital structure is the ratio of the level of current liabilities and ownership of capital. This study aims to provide empirical data on the form of capital subsector cosmetics and household indexed in the Indonesia Stock Exchange. This observation uses descriptive statistical methods represented by the calculation of debt-to-equity ratio (DER). Sampling is carried out using purposeful sampling methods protected by six institutional standards. As a result, we found that the calculation of the total liabilities of the enterprise varies with a deviation from the trend of 87.64. Further research is expected to add variable factors that affect the capital structure of the organization.